2021
DOI: 10.3390/ijms22052764
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Amyloid Burden by Proliferated Homeostatic Microglia in Toxoplasma gondii-Infected Alzheimer’s Disease Model Mice

Abstract: In this study, we confirmed that the number of resident homeostatic microglia increases during chronic Toxoplasma gondii infection. Given that the progression of Alzheimer’s disease (AD) worsens with the accumulation of amyloid β (Aβ) plaques, which are eliminated through microglial phagocytosis, we hypothesized that T. gondii-induced microglial proliferation would reduce AD progression. Therefore, we investigated the association between microglial proliferation and Aβ plaque burden using brain tissues isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Transcriptome studies have indicated that homeostatic microglia gradually adopt a unique phagocytic disease-associated microglia (DAM) phenotype in neurodegenerative disease, chronic inflammation, and advanced aging ( Rangaraju et al., 2018 ). In addition, it has been demonstrated that T. gondii infection induces homeostatic microglial proliferation that reduces Aβ plaque burden in a 5XFAD AD mouse model ( Shin et al., 2021 ), suggesting a sustained supply of homeostatic microglia may help in the resolution of Alzheimer’s and other prion-like neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome studies have indicated that homeostatic microglia gradually adopt a unique phagocytic disease-associated microglia (DAM) phenotype in neurodegenerative disease, chronic inflammation, and advanced aging ( Rangaraju et al., 2018 ). In addition, it has been demonstrated that T. gondii infection induces homeostatic microglial proliferation that reduces Aβ plaque burden in a 5XFAD AD mouse model ( Shin et al., 2021 ), suggesting a sustained supply of homeostatic microglia may help in the resolution of Alzheimer’s and other prion-like neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In the infected group, a significant decrease in the amyloid plaque burden concurrent with an extensive proliferation of homeostatic microglial proliferation and an increased number of plaque-associated microglia were observed. Hence, it was concluded that chronic T. gondii infection can induce microglial proliferation in the brains of mice with progressed Alzheimer's disease, a promising approach for the treatment of this neuropathy [84]. In conclusion, the relationship of T. gondii and the development of Alzheimer's disease and cognitive impairment require further studies on human subjects and animal models [85] to elucidate the possible role of toxoplasmosis in the etiology of Alzheimer's disease.…”
Section: Toxoplasmosis and Parkinson's And Alzheimer's Neuropathiesmentioning
confidence: 99%